The benefits of inclusive education programs on character development of regular students in elementary schools - Utomo Utomo; Hayatun Thaibah (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
The implementation of inclusive education does not only have a positive impact on children with special needs. Moreover, the presence of children with special needs in inclusive education can also be a means to develope character education for regular students. This study uses a qualitative approach. Data collection techniques using interviews, observation, documentation and triangulation then analyzed using an interactive model from Miles and Huberman. The results of the research show that: (1) regular students are able to appreciate the differences. (2) regular students are willing to invite students with special needs to participate in every class activity. (3) the great curiosity of regular students encourages them to ask questions, especially to special assistant teachers regarding the actual condition of students with special needs. (4) regular students give good appreciation to students with special needs when they show their talents and abilities in public. (5) regular students are willing to be invited to make friends and lend their belongings to help students with special needs (6) if something happens that is considered difficult for students with special needs, regular students will immediately help. (7) regular students are able to look after and protect students with special needs.